Biologics for Inflammatory Bowel Disease in Clinical Practice: A Calabria (Southern Italy) Prospective Pharmacovigilance Study - Martina Tallarico; Caterina Palleria; Livia Ruffolo; Rocco Spagnuolo; Maria Diana Naturale; Adele Emanuela De Francesco; Caterina De Sarro; Rossella Romeo; Rita Citraro; Patrizia Doldo; Ludovico Abenavoli; Luca Gallelli; et al. (MDPI AG, 2022)
Background: The use of immune-modifying biological agents has markedly changed the clinical course and the management of Inflammatory bowel diseases (IBDs). Active post-marketing surveillance programs are fundamental to early recognize expected and unexpected adverse events (AEs), representing a powerful tool to better determine the safety profiles of biologics in a real-world setting. Methods: This study aimed to identify the occurrence of AEs and therapeutic failures linked to biological drugs used in gastroenterology units during a prospective pharmacovigilance program in Southern Italy. Patients affected by IBDs and treated with a biologic agent, from 1 January 2019, to 31 December 2021 (study period) in three gastroenterology units were enrolled. Results: Overall, 358 patients with a diagnosis of active Crohn's disease or ulcerative colitis satisfying inclusion criteria have been enrolled. Infliximab (IFX) was the most administered drug at the index date (214; 59.8%), followed by Adalimumab (ADA; 89; 24.9%), Golimumab (GOL; 37; 10.3%), Vedolizumab (VDZ; 17; 4.7%) and Ustekimumab (UST; 1; 0.3%). Seventy-three patients (20.4%) experienced at least one AE, while 62 patients (17.3%) had therapeutic ineffectiveness. No serious AEs were reported in the follow-up period in the enrolled patients. AEs have been described with IFX (50/214; p = 0.47), GOL (7/37; p = 0.78), ADA (13/89; p = 0.18), and VDZ (3/17; p = 0.52), no AEs have been noticed with UST (0/1). Conclusions: Based on the low rate of AEs observed and withdrawal from treatment, our data seem to corroborate the favorable beneficial/risk profile of biologics for IBDs.